2016
DOI: 10.1007/s00213-016-4505-5
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of PKA, PKC, CAMKII, ERK 1/2 pathways is involved in the acute antidepressant-like effect of (octylseleno)-xylofuranoside (OSX) in mice

Abstract: The results demonstrated that OSX showed an antidepressant-like effect in the TST in mice through the activation of protein kinases PKA, PKC, CAMKII and ERK1/2 that are involved in intracellular signalling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Our study found the potential target of miR-1275 (17)(18)(19). Furthermore, many studies have shown that PKCα can play a role in diagnosing cancers (20). In pancreatic cancer, PKCα expression was thought to be directly correlated with tumorigenicity and survival rate (21).…”
Section: Discussionmentioning
confidence: 75%
“…Our study found the potential target of miR-1275 (17)(18)(19). Furthermore, many studies have shown that PKCα can play a role in diagnosing cancers (20). In pancreatic cancer, PKCα expression was thought to be directly correlated with tumorigenicity and survival rate (21).…”
Section: Discussionmentioning
confidence: 75%
“…Disruption in cyclic cAMP-PKA signaling has been implicated in stress maladaptation, anxiety, and depression [ 23 ]. Chronic treatment with fluoxetine enhances cAMP levels, subsequently activates PKA, and upregulates CREB signaling in the hippocampus, cortex, and hypothalamus of the chronically stressed rats [ 27 ]. The previous studies showed that Yueju treatment induced an upregulation of PKA-CREB signaling expression in the KM mice [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoid restored the decrease in the phosphorylation of CaMKII caused by chronic glucocorticoid administration [ 140 ]. Studies using ursolic acid, creatine, ferulic acid, or (octylseleno)-xylofuranoside showed that the reduction of immobility time in the tail suspension test in mice might be reversed by administration of KN-62 (a CaMKII inhibitor) [ 141 , 142 , 143 , 144 , 145 ]. Similarly, the antidepressant-like effect of memantine and 7-fluoro-1,3-diphenylisoquinoline-1-amine in forced swim test in mice was blocked by KN-62 [ 146 , 147 ].…”
Section: Depression-like State In Rodentsmentioning
confidence: 99%